happykiddo
  • happykiddo
A prism has a right triangle as its base with a hypotenuse that measures 5 meters and legs that measure 3 meters and 4 meters. What is the surface area of this prism if the height of the prism is 6 meters? 78 m^2 84 m^2 96 m^2 102 m^2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Jlastino
  • Jlastino
I suck at drawing lol so the problem says that the sides of the triangle are 5,3 and 4 and the height is 6 And we are asked to look for the surface area If you would get the "pieces" of the prism you would get....2 bases (which are triangles) and 3 sides (which are rectangles) the formula for the surface area is 2B+Ph B= area of base (triangle) P=perimeter of base (triangle) h=height There are three sides given for the triangle at the base (3 and 4 as the legs) (and 5 as the hypotenuse) In any triangle, If the side lengths are known then the area of the triangle can be calculated using heron's formula A= sqrt (S*(S-a)(S-b)(s-c) where s is the semi perimeter (meaning half of the perimeter) S=(a+b+c)/2 We need to find s first a=3 b=4 c=5 (3+4+5)/2 12/2 4 Then use that for the equation A= sqrt (S*(S-a)(S-b)(s-c) A=sqrt(6(6-3)((6-4)(6-5) = sqrt ((6(3)(2)(1) sqrt (36) =6 B=6 Now this is the area of the base Now we get the perimeter of the triangle and multiply it by the height The perimeter is the sum of all the sides P=a+b+c =3+4+5 12 then multiply it by 6 (which is the height 12(6) 72 Now back to the equation 2B+Ph SA=2(6) +72 Sa=12+72 =84 :D

Looking for something else?

Not the answer you are looking for? Search for more explanations.